Proclivity to relapse among Malay women: The clients intention and the effectiveness of the rehabilitation programs / Nadhira Ahmad Afip, Iskandar Hassan Tan Abdullah and Tuan Noriani Tuan Ismail - Ahmad Afip, Nadhira; Tan Abdullah, Iskandar Hassan; Tuan Ismail, Tuan Noriani (2021)
In the 20th century, it has been identified that the changes in women's roles such as the growing similarities between the social responsibilities of men and women are some of the factors that contribute toward the increased number of drug abuse among women (Medeiros et al., 2017). In the year 2019, 6,330 Malaysian women have been detected using drugs compared to 125,320 male drug addicts (Agensi Anti-Dadah Kebangsaan, 2019). However, based on the statistic provided by the National Anti-Drug Agency (NADA), the yearly increment of women's involvement in drug abuse is higher compared to men with the percentage of 15.8% and 8.4%. Table 1 shows the distribution of women's involvement in drug abuse based on ethnic. From the table, it can be identified that most women involvement in drug abuse are Malay women compared to other ethnicities.